Optimizing Green Lapak to improve youth economic welfare through herbal beverages - Yona Wahyuningsih; Setyaningsih Rachmania; Yayang Furi Furnamasari (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2025)
Indonesia, as a tropical country, possesses abundant biodiversity, including medicinal plants that hold great potential in supporting both public health and economic resilience. This community service program was conducted in Pegagan Village, Cirebon Regency, in response to the economic downturn and limited employment opportunities faced by local youth due to the COVID-19 pandemic. The main objective of this program was to empower youth through training in the construction and utilization of a Green Lapak (a sustainable planting structure) for cultivating herbal plants that can be processed into traditional health beverages. The methods included several strategic stages: socialization, technical training, field practice, and structured mentoring and evaluation using Focus Group Discussion (FGD) and checklist forms. The results showed that youth participants, organized under the BhoBand community group, gained sufficient knowledge and skills to independently cultivate herbal plants using eco-friendly materials such as bamboo and paranet. This program effectively enhanced local skills, environmental awareness, and economic opportunities. With a collaborative and participatory approach, this initiative has the potential to be expanded as a sustainable economic empowerment model based on local herbal resources.   Abstrak Indonesia sebagai negara tropis memiliki kekayaan hayati, termasuk tanaman herbal yang berpotensi besar dalam menunjang kesehatan dan perekonomian masyarakat. Pengabdian masyarakat ini dilaksanakan di Desa Pegagan, Kabupaten Cirebon, sebagai respons terhadap dampak pandemi COVID-19 yang menyebabkan penurunan pendapatan dan keterbatasan akses pekerjaan bagi pemuda setempat. Tujuan dari kegiatan ini adalah memberdayakan pemuda melalui pelatihan pembuatan Green Lapak sebagai media budidaya tanaman herbal yang dapat diolah menjadi produk minuman tradisional bernilai ekonomi. Metode pelaksanaan pengabdian meliputi beberapa tahapan strategis, mulai dari sosialisasi, pelatihan teknis, praktik pembuatan Green Lapak, hingga pendampingan dan evaluasi melalui diskusi kelompok terfokus dan lembar ceklist. Hasil kegiatan menunjukkan bahwa pemuda yang tergabung dalam komunitas BhoBand mampu memahami dan mempraktikkan budidaya tanaman herbal secara mandiri, memanfaatkan bahan lokal seperti bambu dan paranet dalam pembangunan Green Lapak. Program ini berhasil meningkatkan keterampilan, partisipasi, dan kesadaran lingkungan masyarakat, serta membuka peluang ekonomi baru berbasis potensi lokal. Dengan pendekatan kolaboratif dan partisipatif, pengabdian ini berpotensi dikembangkan lebih lanjut sebagai model pemberdayaan ekonomi berkelanjutan berbasis tanaman herbal. Kata Kunci: COVID-19; kesejahteraan ekonomi pemuda; minuman herbal